Compensatory effects of M. tuberculosis rpoB mutations outside the rifampicin resistance-determining region. Issue 1 (1st January 2021) - Ma, Pengjiao; Luo, Tao; Ge, Liang; Chen, Zonghai; Wang, Xinyan; Zhao, Rongchuan; Liao, Wei; Bao, Lang
ABSTRACT: Mycobacterium tuberculosis has been observed to develop resistance to the frontline anti-tuberculosis drug rifampicin, primarily through mutations in the rifampicin resistance-determining region (RRDR) of rpoB . While these mutations have been determined to confer a fitness cost, compensatory mutations in rpoA and rpoC that may enhance the fitness of resistant strains have been demonstrated. Recent genomic studies identified several rpoB non-RRDR mutations that co-occurred with RRDR mutations in clinical isolates without rpoA/rpoC mutations and may confer fitness compensation. In this study, we identified 33 evolutionarily convergent rpoB non-RRDR mutations through phylogenomic analysis of public genomic data for clinical M. tuberculosis isolates. We found that none of these mutations, except V170F and I491F, can cause rifampin resistance in Mycolicibacterium smegmatis . The compensatory effects of five representative mutations across rpoB were evaluated by an in vitro competition assay, through which we observed that each of these mutations can significantly improve the relative fitness of the initial S450L mutant (0.97–1.08 vs 0.87). Furthermore, we observed that the decreased RNAP transcription efficiency introduced by S450L was significantly alleviated by each of the five mutations. Structural analysis indicated that the fitness compensation observed for the non-RRDR mutations might be achieved by modification of the RpoB active centre or by changes in interactions between RNAP subunits. Our results provide experimental evidence supporting that compensatory effects are exerted by several rpoB non-RRDR mutations, which could be utilized as additional molecular markers for predicting the fitness of clinical rifampin-resistant M. tuberculosis strains.